MINAT MEMBACA PADA MAHASISWA PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Nana Rahayu; Sarah Azizah (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to describe students' reading interest at the Japanese Language Education Program of FKIP, Universitas Riau through Japanese reading texts. The method of this study was a quantitative approach with a sampling technique using a saturated sample technique. The samples of this study were students of the Japanese Language Education Program for the 2020/2021 academic year; the total number of respondents in this study was 30 students. The data were collected using a reading interest questionnaire consisting of 30 statement items. The data collected were analyzed through frequency analysis using SPSS 25.0. The lowest, highest, mean score, and standard deviation values were calculated using hypothetical statistics to help categorize data into low, medium, and high categories. The study results showed that students’ interest in reading Japanese texts was in the medium category with a percentage of 76.7%. The readings mostly liked by students were light readings such as folk tales or children's fairy tales. To conclude, students' reading enthusiasm and motivation were still low, resulting in a lack of positive feelings and attitudes toward Japanese reading.